Aspergillus fumigatus produz vesículas extracelulares biologicamente ativas capazes de estimular a resposta imune in vitro e in vivo. Caracterização estrutural e funcional - Jéssica Amanda Marques Souza (2019)
The release of biomolecules by cells of different organisms have been associated with the secretion of extracellular vesicles, an evolutionarily conserved mechanism considered a potent vehicle of intercellular communication. Recent studies demonstrated that EV liberation from many microorganisms, including pathogenic fungi, is associated with the physiology and pathogenicity of these microorganisms. In this work we isolated, for the first time, EVs produced by A. fumigatus, an ubiquitous and saprophytic organism, considered an important pathogen in immunocompromised patients. The first structural EVs characterizations from A. fumigatus demonstrated a production of circular bilayer structures, a characteristic of EVs, with 100 to 200 nm diameter. A. fumigatus EVs have ergosterol and a protein burden very diverse, containing proteins related to the remodeling of cell wall and metabolism, and proteins involved in virulence like REDOX proteins and allergens. We demonstrated that phagocytes are able to internalize A. fumigatus EVs, and the sensitization of phagocytic cells (macrophages and bone-marrow derived neutrophils – BMDN) with EVs, before fungus challenging, resulted in an increasing of phagocytic capacity culminating in a higher clearance of the fungal pathogen. It was also demonstrated that EVs of this fungus are able to induce production of TNF-α and CCL2 by macrophages and an additive effect was observed in production of these mediators when the cells were challenged with conidia. In EVs sensitized BMDN, there was an increase in TNF-α and IL-1β production after conidia exposure. Moreover, in an animal immunization model with EVs from A. fumigatus, there was a reduction in inflammatory infiltrate to alveoli of animals after intranasal infection with A. fumigatus conidia. The immunization also conferred a reduction in production of the pro-inflammatory mediators IL-β, IL-6 and CXCL1, and a slight increase of IL-17 after infection. The decrease of IL-1β in immunized animals was corroborated by a lower activation of inflammasome, characterized by a lower activation of caspase-1. We also evaluated the participation of proteins from ESCRT complex in A. fumigatus EVs biogenesis. We observed a positive regulation of protein expression in all ESCRT complexes during the A. fumigatus growth for up to 48 hours, suggesting the participation of those complexes in EVs secretion in this fungus. Taken together, we demonstrated that A. fumigatus produces biologically active EVs that are able to impact in immune and inflammatory response, both in vitro and in vivo, increasing the fungal clearance and decreasing the inflammatory response. In this sense, A. fumigatus EVs may represent a new target for the formulation of prophylactic methods against aspergillosis.